Exploring Canadian High School Sport Coaches' Perspectives on Social Justice Issues - Bishop, Evan (Université d'Ottawa / University of Ottawa, 2026)
For adolescents, sport is an incredibly potential-filled activity. In Canada, school sport offers youth opportunities to participate in a wide variety of organized after-school sports (School Sport Canada, 2025). When sport is structured appropriately (i.e., with regard to safety and adequate learning opportunities) and led by competent/caring coaches (Camiré, 2014), sport can play an impactful role in facilitating positive physical and psychosocial development among young athletes. Despite the positive outcomes associated with sport participation, social justice issues - such as racism, gender inequity, and ableism - continue to exist in Canadian school sport. Crucially, recent research has highlighted the limits of popular coaching approaches to address social justice issues (Gonzalez et al., 2020; Camiré, 2022). More inclusive sport spaces are needed to ensure all students have access to safe experiences (Coakley, 2016; Kochanek & Erickson, 2019). The purpose of this dissertation is to explore coaches' attitudes, perspectives, perceived roles, and intended actions related to social justice in Canadian high school sport. The four articles included in the present dissertation present a compelling narrative that highlights the complex and uncertain facets of Canadian high school coaches' attitudes and activism towards social justice. Article 1 presents an introductory exploration of coach attitudes toward social justice, examining some of the statistical associations between coaches' understandings of white privilege and other important social justice issues (e.g., racism, support for persons living with a disability). Quantitative analyses were performed to derive trends that served as an ideal starting point to the overarching topic of study for this dissertation. Article 2 presents an overview of coaches' perceived challenges and recommendations related to social justice within their teams, schools, and school boards. A qualitative content analysis highlighted the wide range of social justice perspectives that coaches possessed. This article highlights how many social justice issues are missed or ignored, nuancing some of the results from article 1. Article 3 presents an in-depth exploration of coaches' social justice attitudes through semi-structured individual interviews. Thematic and narrative-inspired analyses showed the contradictory attitudes that many coaches possessed with regard to social justice activism (e.g., supportive of anti-racism, yet still exhibiting sexist attitudes). Building on articles 1 and 2, the results from article 3 showed how awareness of social justice issues does not necessarily translate into proactive and transformative social justice activism. Article 4 concludes the dissertation and departs, paradigmatically-speaking, from the conventional humanist approaches taken in articles 1, 2, and 3. The main aim of this article is to examine the opportunities and tensions of journeying into postqualitative inquiry (PQI) in sport and exercise psychology. By exploring my own PQI-related experiences as a doctoral student, I offer suggestions for how graduate students can attempt to integrate post philosophies in their studies. Article 4 complements articles 1, 2, and 3 by engaging in a discussion about how PQI can open space for more just inquiry in the coaching (and sport) sciences. In sum, articles 1-4 tell a story that complexifies our understanding of social justice by highlighting how knowledge about social injustices is not the only factor required to drive a person to engage in social justice activism, advocacy, or allyship. Forces that go beyond knowledge must be acknowledged if people are to proactively engage in social justice activism, which has important implications for coaching practice. This dissertation, which navigates within and beyond conventional humanist research practices, seeks to explore different ways through which people (including coaches) can connect with and act on social injustices. By moving beyond conventional humanist research practices, this dissertation contributes to the literature by advocating for ontological pluralism in coaching science research.
Keywords: Coaching; Social Justice; Ontological Pluralism; Postqualitative Inquiry